2007
DOI: 10.4141/p06-078
|View full text |Cite
|
Sign up to set email alerts
|

White mulch and a south facing position favour strawberry growth and quality in high latitude tunnel cultivation

Abstract: Karhu, S. T., Puranen, R. and Aflatuni, A. 2007. White mulch and a south facing position favour strawberry growth and quality in high latitude tunnel cultivation. Can. J. Plant Sci. 87: 317-325. Polyethylene mulches with black or white surface were compared in seven strawberry (Fragaria × ananassa Duch.) genotypes in a 2-yr experiment. The plants were covered by an unheated walk-in tunnel at the beginning of the first harvest season. The effects of a south-west versus north-east position of plants within the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Seasonal variations in strawberry yield productivity with mulching were found in earlier studies (Karhu et al 2007;Soliman et al 2015). Compared to the un-mulched plants, Soliman et al, 2015, reported that 'Festival' fruit yield was significantly higher with black plastic mulch treatment in the first season only.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Seasonal variations in strawberry yield productivity with mulching were found in earlier studies (Karhu et al 2007;Soliman et al 2015). Compared to the un-mulched plants, Soliman et al, 2015, reported that 'Festival' fruit yield was significantly higher with black plastic mulch treatment in the first season only.…”
Section: Discussionsupporting
confidence: 57%
“…The effect of black plastic mulching on the fruit yield could be attributed to the increasing soil temperatures and water conservation while facilitating the weed-free environment (Pandey et al 2015;Singh and Kamal 2012;Tarara 2000). This is in agreement with the results of mulching in strawberry and tomato crops (Karhu et al 2007;Singh and Kamal 2012;Soliman et al 2015). Compared to un-mulched plants, the yield of tomato plants was increased by 20.7-29.8% in black mulch treatment (Singh and Kamal 2012).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results were analyzed statistically using the program (SAS V 9.0, 2002), and averages were compared according to Duncan's tests at the probability level (0.05). The following characteristics were studied: 1-Leaves content of chlorophyll (SPAD): using a field device (502 -Chlorophyll Meter SPAD) [17].…”
Section: Methodsmentioning
confidence: 99%
“…Where the seedlings were treated by watering them with Acadian seaweed extract at two concentrations (4, 8 g/l), spraying with boron at two con-centrations (30 and 60 mg /l of boric acid) and foliar spraying with two concentrations of zinc (50 and 100 mg /l zinc sulfate) in addition to Control treatment (untreated plants). Randomized Complete Block Design (R.C.B.D) was used to implement the experiment, with three replicates (Karhu et al, 2007).…”
Section: Methodsmentioning
confidence: 99%